Short versus long duration mobility in vocational education and training - Santos, Miguel Baião dos (2020)
VET learner´s mobility abroad is slowly getting importance to the individual employability. From 2014 until 2020 the VET mobility in Erasmus+ scope had financed almost one million mobilities. For VET institutions,companies, learners, and families the challenge is to have an efficient mobility that triggers the learner´s employability, giving an added value to the CV. However, the choice relays mainly on the alternative on short duration mobility or long duration mobility. What is the best option for the several actors? What benefits and constraints may arise in both durations? We have made an extensive revision of bibliography in order to answer these questions and help learners, companies, VET institutions and society to take smart decisions.